Perception on Multiple Choice Questions: Its Challenges and Implication Among Grade 12 Senior High Students of Mindanao State University-Sulu - Salha U. Amil (HM Publisher, 2022)
This study investigated the perception on Multiple Choice Questions: Its challenges and implications among Grade 12 Senior High Students of Mindanao State University-Sulu. Descriptive survey method was used in this study. Random sampling was used to select 100 students, 50 from GAS strand and 50 from STEM strand Grade 12 Senior high school students. The researcher prepared a survey questionnaire to obtain the necessary data. Mean was used to analyze the perceived challenges and implication while an independent T-test sample was used to test the hypotheses at alpha level of 0.05.The following were the highlight of the study: Multiple Choice Questions is a test format only used as an assessment tool during their Quarterly Examinations and it was revealed that MCQ is challenging foremost due to the need to answer critically under time pressure. Consequently, they need to manage their time in order to answer every subject. The challenge of MCQ also lies in the difficulty of the subject Also, the result revealed the implications of MCQ tends to urge students to answer each subject at limited time pressure students that they experience test anxiety. Meanwhile, there is a need to look into the level of difficulty of the subject matter which requires student rigorous preparation before exam. More so, MCQ develop student’s analysis on problem solving which provides them a real time experience of taking major exams and develop time management in studying and strategies in answering as it encourages them to answer with persistence and resilience. The study recommended that the school administration should encourage the applicability of this test format to other colleges in the institution that require licensure examination, Setting programs and intervention for the improvements of this endeavour and Creating more research studies.